Optimization of Natural Gas Network Operation under Uncertainty - Elbashir, Nimir O.; El-Halwagi, Mahmoud M.; Economou, Ioannis G.; Hall, Kenneth R.; Ogbe, Emmanuel; Elkamel, Ali; Fowler, Michael; Almansoori, Ali (Natural Gas Processing from Midstream to Downstream, 2019)
This chapter reviews the modeling and optimization efforts in natural gas network systems, with attention to blending natural gas from various sources under steady‐state conditions. The mixing of natural gas from diverse sources, with different quality specifications, leads to a mixed‐integer nonlinear programming formulation for the problem, which is solved using a global optimization approach. The chapter highlights strategic and tactical decision issues related to design and operation of natural gas network systems. It implements a two‐stage stochastic programming approach to handle uncertainty associated with the design and operation of natural gas networks. The chapter presents a case study of the Ontario natural gas pipeline system in southern Canada, to demonstrate the proposed approach. The results from the case study suggest implementing various design configurations and operational conditions for different uncertainty realizations. The chapter only considers a monolithic approach of solving a large‐scale optimization problem under uncertainty.